Psychiatric Influences on Hidradenitis Suppurativa: A Call for Help - Shan, Holly D.; Huffman, Samuel S.; Bovill, John D.; Haffner, Zoë K.; Towfighi, Parhom; Benedict, Carol D.; Evans, Karen K. (Archives of Plastic Surgery, 2024)
Background Hidradenitis suppurativa (HS) is associated with a high prevalence of psychiatric disorders. However, no studies examine how psychiatric disorders influence surgical and financial outcomes. This study aimed to assess impact of a psychiatric diagnosis on patients treated for HS.Methods Patients with HS were retrospectively identified at a single institution from 2010 to 2021. Cohorts were stratified by the presence of a psychiatric disorder. Demographics, comorbidities, and disease characteristics were collected. Outcomes assessed included the procedural interventions and emergency department (ED) visits. Financial distress was assessed via the COST-FACIT Version 2 survey.Results Out of 138 patients, 40 (29.0%) completed the survey of which 19 (47.5%) had a preexisting psychiatric diagnosis. No demographic differences were found between cohorts. Mean follow-up was 16.1 ± 11.0 months. The psychiatric cohort had a higher median number of surgeries received (7.0 vs. 1.5, p < 0.001), a higher median number of ED visits (1.0 vs. 0, p = 0.006), and a similar hospital length of stay (p = 0.456). The mean COST-FACIT score of the overall study population was 19.2 ± 10.7 (grade 1 financial toxicity). The psych cohort had a lower mean COST-FACIT score (16.8 vs. 21.3, p = 0.092) and reported greater financial hardship (3.3 vs. 1.7, p < 0.001). On multivariate analysis, a psychiatric diagnosis was predictive of lower credit scores, more ED visits, and a higher number of surgeries.Conclusion Preexisting psychiatric conditions in patients with HS are associated with increased health care utilization and surgical intervention with substantial financial distress. Plastic surgeons should be cognizant of such comorbid disorders to facilitate holistic care addressing all patient needs.
Keywords: hidradenitis suppurativa; anxiety; depression; psychiatric comorbidities; financial stress